1993
DOI: 10.1073/pnas.90.19.8876
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal anti-idiotypic antibodies as functional internal images of enzyme active sites: production of a catalytic antibody with a cholinesterase activity.

Abstract: Monodonal antibody 9A8 was selected by immunizing mice with AE-2, a monodonal antibody directed against the active ite of acetylchoilnesterase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(60 citation statements)
references
References 21 publications
1
59
0
Order By: Relevance
“…The proposal is supported further by the successful application in obtaining antibodies with cholinesterase-like (9) and ␤-lactamase activities (10). Specifically, mice immunized with a monoclonal IgG, AE-2, that displayed both high specificity to the active site of human erythrocyte acetylcholinesterase (AcChoE) and strong inhibition of the enzyme activity produced a monoclonal IgM (antiidiotype) with activity similar to that of the parental enzyme (9).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…The proposal is supported further by the successful application in obtaining antibodies with cholinesterase-like (9) and ␤-lactamase activities (10). Specifically, mice immunized with a monoclonal IgG, AE-2, that displayed both high specificity to the active site of human erythrocyte acetylcholinesterase (AcChoE) and strong inhibition of the enzyme activity produced a monoclonal IgM (antiidiotype) with activity similar to that of the parental enzyme (9).…”
mentioning
confidence: 76%
“…We have demonstrated previously that the hydrolytic activity of 9A8 is characterized by a relaxation of specificity toward both substrates and inhibitors as compared with AcChoE (9). A specific feature of serine esterases, and of AcChoE in particular, is the specific irreversible inhibition by organophosphorous compounds (19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunization of autoimmune-prone MRL-lpr/lpr mice with DNA-protein complexes also results in significantly higher production of anti-DNA Abs and abzymes with DNase activity comparing with nonautoimmune CBA and BALB/c healthy mice [29][30][31]. At the same time, artificial antiidiotypic abzymes can be induced by immunization of animals with different enzymes [23][24][25][26][27][28]. It was first suggested that natural SLE DNase Abzs may be antiidiotypic abzymes to topoisomerase I [53].…”
Section: Introductionmentioning
confidence: 97%
“…At the same time, some antiidiotypic Abs against active centers of many enzymes are also catalytically active [8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Healthy humans do more often not demonstrate catalytic Abs or their activities are extremely low.…”
Section: Introductionmentioning
confidence: 99%